COMPARATIVE STUDY ON LACTATE DEHYDROGENASE,ALKALINE PHOSPHATASE AND IMMUNOGLOBULINS INSERUM AND SALIVA OF ACUTE LEUKEMIA AND ORALSQUAMOUS CELL CARCINOMA PATIENTS - Merza, Khalida; Alaaraji, Sanad; Abdullah, Bashar (Iraqi Journal of Science, 2024)
Biochemical changes have been occurring in biological fluids and tissues ofdifferent types of malignancies. Most molecules found in blood and urine are foundin saliva, but their concentrations were estimated to be one tenth to one thousandthof that in the blood.The present study aims to measure the levels of Lactate dehydrogenase & Alkalinephpsphatase enzymes and Immunoglobulins in serum and saliva of Acute Leukemia(AL) and Oral Squamous Cell Carcinoma (OSCC) patients, and apparantly healthyindividuals as control group.Unstimulated (resting) saliva and serum were collected from 70 newly diagnosed,untreated AL patients and 20 OSCC patients, in addition to 20 healthy individualsand 12 adults with periodontitis.According to the results of this study, serum and saliva enzymes showed asignificant increase in Lactate Dehydrogenase (LDH) and Alkaline Phosphatase(ALP) levels of AL and OSCC in comparison to control group. Serum and salivaIgG showed non significant increase, whereas IgA level was reduced and IgMshowed significant increase in AL patients in comparison to the control group.Results on OSCC patients showed a significantly increase in serum and salivaimmunoglobulins but saliva IgA was reduced in comparison to control group.The levels of serum LDH and ALP in AL patients were higher than that in OSCCpatients, whereas the levels of saliva LDH and ALP in AL were lower than that ofOSCC patients. The serum IgG and IgM levels were higher in AL patients than thatof OSCC patients, whereas serum IgA was lower in AL patients. Salivaimmunoglobulins were higher in OSCC patients than that of AL patients.In conclusion, a disseminates malignancy, like AL, causes changes in the levels ofLactate dehydrogenase and Alkaline phosphatase in blood as well as in saliva.However, the changes in blood are more striking than that is saliva while in a localmalignancy like OSCC, the changes are more prominent in saliva than that in blood.